Soil Carbon Sequestration in Nothofagus obliqua Forests with Different Canopy Cover Levels Under Silvopastoral Management - Camila Ramos; Erick Zagal; Salme Timmusk; Francis Dube; Leandro Paulino; Juan Ortiz; Jean Intriago-Ávila; Juan Pablo Fuentes (Agronomy)
Agroforestry contributes to slowing deforestation, favoring ecosystem regeneration and improving land use sustainability. This study evaluated the impact of silvopastoral systems on soil recovery and their capacity to sequester and stabilize carbon (C) and nitrogen (N) in degraded soils of a native Nothofagus obliqua forest in Ranchillo Alto (37°04′52″ S, 71°39′14″ W), Ñuble Region, Chile. Three open (Op), semi-open (SOp), and semi-closed (SC) silvopastoral systems were analyzed and compared with a control (Ctr) without silvopastoral management across four soil depths (0–10, 10–20, 20–30, 30–60 cm). Physical, chemical, and biological analyses were performed, along with soil physical organic matter (SOM) fractionation. The highest C levels were found in the 0–10 cm depth (13.9, 11.8, 11.5, and 8.5% for Op > SC > SOp and Ctr, respectively). Despite its higher degradation, Op presented the highest levels of C, N, and non-oxidizable C (Cnox), possibly due to pyrogenic carbon from old potato burns. Furthermore, the same trend was observed for mineral associated organic matter (MAOM) fraction and C stocks in all silvopastoral systems compared to the control. These results underline the potential of silvopastoral practices to improve soil quality and increase long-term carbon sequestration, contributing to sustainable soil restoration strategies.